IMPLEMENTASI PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) DALAM MEREALISASIKAN LINGKUNGAN RAMAH PEREMPUAN DAN PEDULI ANAK KABUPATEN NAGAN RAYA - Fitriati, Cut Annisa; Safrida, Safrida; Pratama, Agus; Marefanda, Nodi (Dialogue : Jurnal Ilmu Administrasi Publik, 2023)
The increase in cases of violence against women and children in Nagan Raya Regency over the past few years has led to a mission to establish a women-friendly and child-caring environment through various efforts. One of them is through the implementation of the Family Learning Center Program (PUSPAGA) as a forum for the prevention and resolution of cases that occur within the family. This study uses a qualitative method by collecting data on PUSPAGA at the district and village levels, which aims to see the obstacles and barriers to implementation that occur in the field. The results of the study show that implementation constraints lie in the aspects of insufficient budget and human resources, lack of promotion of program introduction to the community and overlapping responsibilities of the village PUSPAGA implementers. Follow-up on these obstacles can be resolved through determining the right priority management by the district and village PUSPAGA implementers in optimizing program implementation.